Alle origini dell’iconografia garibaldina: note su alcune rappresentazioni dell’eroe tra il 1848 e la Seconda Guerra d’Indipendenza - Susanna Arangio (Annali Online dell'Università di Ferrara. Sezione Lettere)
This paper proposes an excursus of the major images that have Giuseppe Garibaldi like a principal subject, made between the 1848, when he came back Italy, and the 1859, when he fought in the Second Italian War of Independence. It is a problematic question because, after the defeat of Roman Republic in 1849, he spent almost ten years in exile and during that period the censorship was very strong in almost all the Italian peninsula. Nonetheless in this period we already find many of the features of the different Garibaldi’s iconography; at first the popular origin and then a certain malleability that makes his character adaptable in different political and social contexts.